2020
DOI: 10.1177/2050640620917804
|View full text |Cite
|
Sign up to set email alerts
|

Time to diagnosis of symptomatic gastric and oesophageal cancer in the Netherlands: Where is the room for improvement?

Abstract: Background An efficient diagnostic pathway and early stage diagnosis for cancer patients is widely pursued. This study aims to chart the duration of the diagnostic pathway for patients with symptomatic oesophageal and gastric cancer, to identify factors associated with long duration and to assess the association of duration with tumour stage at diagnosis. Methods This was a retrospective cohort study, using electronic health records of six routine primary care databases covering about 640,000 patients, partly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…A similar pattern was reported for esophageal and gastric cancers in a retrospective cohort study from the Netherlands. Whereas patient and secondary care intervals were similar or longer than patient and hospital intervals for our nonpandemic esophageal and gastric cancers, median PC intervals of the Dutch study were substantially shorter than PC/ED intervals reported here 39 …”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…A similar pattern was reported for esophageal and gastric cancers in a retrospective cohort study from the Netherlands. Whereas patient and secondary care intervals were similar or longer than patient and hospital intervals for our nonpandemic esophageal and gastric cancers, median PC intervals of the Dutch study were substantially shorter than PC/ED intervals reported here 39 …”
Section: Discussioncontrasting
confidence: 59%
“…However, owing to the length of patient intervals in the early COVID period, the relative increase of PC/ED intervals during this period was only 18%. On closer examination of nonpandemic data, it became apparent that median PC/ED intervals contrasted sharply with median PC intervals reported in other world regions 37‐39 . By analyzing nearly 11 000 patients aged at least 15 years who presented with symptoms to PC in England and were subsequently diagnosed with one of 28 common and less common cancers, data from a national audit showed that, while varying by cancer type, median patient intervals were significantly longer than PC intervals for 18 of 28 cancer types, which included those analyzed here 37 .…”
Section: Discussionmentioning
confidence: 81%
“…Mean patient interval was 29 days (comparable for patients with and without alarm symptoms), primary care interval 12 days, secondary care interval 13 days, and diagnostic interval 31 days. Absence of cancer‐specific alarm symptoms was associated with “long duration” of primary and secondary care interval 21 …”
Section: Esophagus Stomach and Hpmentioning
confidence: 99%
“…Among the almost 6000 abstracts submitted to 2019 and 2020 UEGWeek editions, 32 were then accepted as full‐text publication to UEG Journal 1–31 . Here we will summarize these “hot” papers (see also Figure 3).…”
Section: Introductionmentioning
confidence: 99%
“…5 In this issue of the United European Gastroenterology Journal, van Erp and colleagues evaluated the duration of different intervals in the diagnostic pathway of gastroesophageal cancer. 6 In this retrospective registry-based study, the authors identified patients registered with oesophageal or gastric cancer in the databases of six large general practice networks in The Netherlands. An attempt was made to reconstruct the diagnostic pathway through record linkage with the Netherlands Cancer Registry including information on clinical tumour stage.…”
mentioning
confidence: 99%